KLASIFIKASI KEKRITISAN LAHAN DI DAS DUA LAUT PROVINSI KALIMANTAN SELATAN - Ratna Liana Dewi; Muhammad Ruslan; Syarifuddin Kadir (Universitas Lambung Mangkurat, 2020)
The condition of critical land in Indonesia both inside and outside the forest area is very concerning. Determination of critical land refers to land that has been damaged due to loss of vegetation cover so as to lose its function as water retention, erosion control, nutrient cycle, micro climate regulator and carbon retention. The rate of forest destruction in South Kalimantan Province is highly varied, one of which is indicated by the increase of critical land area, both inside and outside the forest area. The number of critical watersheds is indicated by the increasing number of natural disasters around the watershed. Improper land use causes increased watershed degradation. This study aims to analyze the level of land criticality in the Dua Laut watershed. The research method is literature study, purposive sampling, overlay and field observation. Data analysis used is Focus Group Discussion (FGD) and Universal Soil Loss Equation (USLE). The results of research on land criticality on various land cover in UL1 forest are somewhat critical of 1 ha and UL7 rather critical 85 ha. Closure of UL2 scrublands is very critical area of 0.2753 ha, UL4 critical area of 1 ha, critical UL6 of 14 ha, UL10 is very critical for 2 ha, UL12 is very critical for 2 ha. Closure of UL3 potential critical rubber garden area of 2 ha, UL5 critical potential covering 62 ha, UL9 somewhat critical for 1099 ha and UL11 rather critical area of 41 ha. On very critical UL8 open land covering an area of 1 ha.Keywords : Critical Land; Land Cover